Itikad Baik Dalam Pelaksanaan Perjanjian (Suatu Kajian Yuridis) = Good Faith in Agreement Implementation (A Juridical Study) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
This research aims to know the implementation of good faith in agreement implementation and the role of a judge in the judgement of agreement implementation based on good faith. It is descriptive and analytical and aims to obtain a comprehensive description of good faith in agreement implementation. Adopting a normative legal approach, it intends to identify the principle, norm or das solen and behaviour or das sein by means of researches in the library and the field. The instrument for data collection is a document study to obtain the secondary data and interview guideline for the primary data. A purposive sampling method is used by means of regarding the appli-cation of the Article 1338 (3) of the Civil Code in some verdicts that have absolute legal forces. The same method is used in deciding the respondents by basing on a certain criterion according to the research objectives. The research results show that good faith in agreement implementation has not been well respected. There are many violations such as breaking the promise, or breaking the laws by not fulfilling the agreement content by one of the parties. Good faith in agreement implementation according to the Article 1338 (3) of the Civil Code is applied by the judge, depending on each individual case through law invention. The judge has a strategic role, for he will apply the Article 1338 (3) of the Civil Code according to the need and social dynamic. Therefore, the judge is not only enforcing the law, but also playing the role of inventing (renewing) the law.